AGRICULTURAL WORKERS AND BURDEN OF MORBIDITY: A COMMUNITY-BASED CROSSSECTIONAL STUDY IN A RURAL BLOCK OF WEST BENGAL - DHIRAJ BISWAS; ISHITA SARKAR; PRAFULLA CHANDRA PAL; NIRMALYA SINHA; SANJAYA KUMAR SAHOO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Agriculture is one of the most hazardous occupations in developing and industrialized countries. Most agricultural workers in developing countries have poor housing conditions and an inadequate diet and are exposed to both general and occupational diseases. The study was undertaken to find out the prevalence of occupational morbidity and its associated risk factors among agricultural workers in a rural Block of West Bengal. Methods: The study was conducted among agriculture workers of Habra Block-I of the state of West Bengal. Multistage random sampling method was followed to select a total of 302 individuals who were distributed among the four villages according to the Probability Proportional to Size (PPS) method. Results: The majority of workers (58.6%) were suffering from nutritional pallor/anemia and dental carries/dental stains were 45.4%. Among other morbidities, 42% of workers were suffering from respiratory morbidity, 26.8% of workers were suffering from cardiovascular diseases, and 26.5% were suffering from hypertension. Duration of work (more than 8 h/day) was significantly associated with morbidity also other covariates such as age, sex, type of family, smoking status, and alcohol consumption had significant effects on morbidity among agriculture workers in both bivariate and multivariable linear regression. Conclusion: This research revealed not only the high prevalence of morbidities among the study population but also the occurrence of a large population with modifiable risk factors such as alcohol consumption, smoking, high load and long duration of work, poor personal hygiene, and non-use of personal protection equipment; the latter, if taken care, will reduce the morbidities of the agriculture workers.